2016
DOI: 10.1021/acs.chemmater.6b00824
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Molecular Structure Dependent Charge Transfer between Isoindigo-Based Polymers and Fullerene

Abstract: The effects of the oligothiophene length of two thiophene-isoindigo copolymers on film morphology, charge transfer, and photovoltaic device performance are reported. Despite the similarities in their repeat unit structures, the two polymers show distinctly different film morphologies and photovoltaic performance upon blending with PC71BM. We found that there is a significant increase in the dielectric constant of the photoactive film upon blending fullerene with the polymer that exhibits a higher power convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…We used two thiophene–isoindigo copolymers, poly(terthiophene‐ co ‐isoindigo) P(T3‐iI) and poly(thiophene‐ co ‐isoindigo) P(T1‐iI), to study the effects of the oligothiophene length on device performance and dielectric properties. We previously showed that, in devices made using P(T3‐iI):PC 71 BM, we see no large‐scale phase separation and a high PCE of 6.1%, whereas in devices made using P(T1‐iI):PC 71 BM large scale phase separation exists in the active layer and the PCE remains at 2.6% . In addition to device performance and film morphology, dielectric constant was also found to be affected by the oligothiophene length with the P(T3‐iI):PC 71 BM blend having a dielectric constant of 4.8 ± 0.1 and P(T1‐iI):PC 71 BM a dielectric constant of 4.2 ± 0.2.…”
Section: Resultsmentioning
confidence: 96%
“…We used two thiophene–isoindigo copolymers, poly(terthiophene‐ co ‐isoindigo) P(T3‐iI) and poly(thiophene‐ co ‐isoindigo) P(T1‐iI), to study the effects of the oligothiophene length on device performance and dielectric properties. We previously showed that, in devices made using P(T3‐iI):PC 71 BM, we see no large‐scale phase separation and a high PCE of 6.1%, whereas in devices made using P(T1‐iI):PC 71 BM large scale phase separation exists in the active layer and the PCE remains at 2.6% . In addition to device performance and film morphology, dielectric constant was also found to be affected by the oligothiophene length with the P(T3‐iI):PC 71 BM blend having a dielectric constant of 4.8 ± 0.1 and P(T1‐iI):PC 71 BM a dielectric constant of 4.2 ± 0.2.…”
Section: Resultsmentioning
confidence: 96%
“…To further investigate the charge generation dynamics in the films studied herein, transient PL measurements were also carried out. It has been previously shown that in many cases when blending a polymer donor with an electron acceptor a biexponential decay is observed in the transient PL spectrum . A fast initial decay on a sub‐50 ps timescale is assigned to nonradiative decay of excitons to the charge‐transfer (CT) states formed at the D‐A interface, which in turn leads to fast exciton dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Systems based on cyano‐containing polymers show higher dielectric constants (4.8 ± 0.2 for DTS‐TPD‐C8‐CN and 4.7 ± 0.2 for DTS‐TPD‐C4‐CN) than those based on the noncyano‐containing parent polymers (4.0 ± 0.1 for DTS‐TPD‐C8 and 3.5 ± 0.1 for DTS‐TPD‐C4). The effect of blending on dielectric constant has been investigated in our previous studies . It has been found that the blend dielectric constant is determined by polymer–fullerene interaction resulting in a change in the dielectric environment of the blend, which leads to a significant increase in dielectric constant in the blend upon blending the polymers with fullerene.…”
Section: Resultsmentioning
confidence: 99%